Gendering migration, livelihood and entitlements: Migrant women in Canada and the United States - Monica Boyd; Deanna Pikkov (United Nations Research Institute for Social Development (UNRISD), 2005)
The United States and Canada have long histories of large-scale migration, and they continue to welcome large flows of legal immigrants. Women make up an increasing proportion of these international flows. In both countries, the majority of legal immigrants are eligible for full citizenship rights and entitlements, with rapid or automatic access to both political rights and labour markets, although stratified entitlements are present for temporary and irregular migrants, and in the realm of social provision. Formally, women partake of these rights equally with men, but gender inequality persists both in government policy and in labour markets. In both countries, moreover, recent political and policy environments are influenced by neoliberal ideological principles, contributing to changes in migration policy, labour markets and social provisions that make female migrants increasingly vulnerable to structural inequalities. In the first part of the paper, migration regimes in the two countries are compared. Women are entering both countries in increasing numbers, though still primarily as dependants of men. Changes to migration policy that increasingly favour admissions of highly educated migrants have been enacted more extensively in Canada; entry in high-skill 'economic' categories now exceeds entry through the humanitarian categories of family reunification and refugee asylum. Admission requirements that emphasize human capital penalize women who come from countries in which resources are highly concentrated in male hands. In the United States, humanitarian category entries still predominate, although high-skill temporary entry increasingly functions as a 'back door' route to permanent status. In the realm of refugee admissions, changes in rules that govern refugee selection have increased gender sensitivity in Canada, but the numbers affected remain low. In both countries, numbers of migrants within temporary categories of entry have increased over the last decade. Women are present in temporary categories that encompass both high and low skill streams, with very different prospects depending on labour market location. Recent policy initiatives in both countries propose the granting of temporary status to irregular migrants; such proposals have the potential to move North American migration regimes closer to European 'guest worker' models, even as these models have proved untenable in Europe. Next, gendered work environments are examined. In the United States and Canada, deregulation of labour markets has reinforced gendered occupational hierarchies in which immigrant women often hold disadvantaged places...
Keywords: 330